Field trials of medical decision-aids: potential problems and solutions. - Wyatt, J. (American Medical Informatics Association, 1991)
Only clinical trials can assess the impact of prototype medical decision-aids, but they are seldom performed before dissemination. Many problems are encountered when designing such studies, including ensuring generality, deciding what to measure, feasible study designs, correcting for biases caused by the trial itself and by the decision-aid, resolving the "Evaluation Paradox", and potential legal and ethical doubts. These are discussed in this paper.